Penguatan Kapasitas Petani dalam Memanfaatkan Cendawan Endofit sebagai Biostimulan Tanaman Padi Melalui Penyediaan Inokulum - Yustisia, Dian; Daniati (LOSARI DIGITAL, 2025)
This community service activity aims to enhance the capacity of farmers in utilizing endophyte fungi as a biostimulant for rice plants through training, assistance, and provision of inoculum. Endophyte fungi are known to stimulate plant growth, increase nutrient absorption, and suppress diseases. The activity partner is the farmers' group 'Bonto Manai' in Saukang village, Sinjai district, which has been relying on chemical fertilizers and pesticides. The implementation methods include socialization, technical training, demonstration plots (demplot) and evaluation through pre-test, post-test, and observation. The results of the activities showed an increase in farmers' knowledge of 78% (average pre-test score of 42 increased to 75 in the post-test). The demonstration plot results showed better rice growth (average plant height of 72 cm) and lower blast disease intensity (8%) compared to the control (18%). This program proves that the use of endophytes can be practically applied by farmers and has the potential to reduce dependence on chemical inputs.